2009
DOI: 10.1111/j.1399-0012.2008.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of central venous catheter‐related thrombosis in living liver donors: how can the risk be minimized?

Abstract: A central venous catheter (CVC) is commonly used for intraoperative management by anesthetists and surgeons during major operations, including donor operations for living donor liver transplantation (LDLT), in which donor safety is of utmost importance. Reasons for use of CVC for donors include measurement of central venous pressure and drug infusion when necessary. A potentially serious complication of a major operation is pulmonary thromboembolism. We report two cases of LDLT donors complicated by catheter r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Moreover, blood loss was similar in donors with and without CVP monitoring, suggesting CVP monitoring may not be necessary [22]. Importantly, central venous catheterisation via the internal jugular or subclavian vein is associated with its own morbidity [24,25], and central venous catheterrelated thrombosis has been observed in living liverdonors [26]. Taken together, these findings suggested that a low CVP technique may not have advantages during living-donor hepatectomy.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, blood loss was similar in donors with and without CVP monitoring, suggesting CVP monitoring may not be necessary [22]. Importantly, central venous catheterisation via the internal jugular or subclavian vein is associated with its own morbidity [24,25], and central venous catheterrelated thrombosis has been observed in living liverdonors [26]. Taken together, these findings suggested that a low CVP technique may not have advantages during living-donor hepatectomy.…”
Section: Discussionmentioning
confidence: 93%
“…To prevent thrombosis that cannot be predicted by screening, routine use of elastic stockings and early ambula-tion are necessary. In addition, the risk from use of a central venous catheter in donors was recently shown in another report from our institute (21). Thus, it is important to carefully consider the use of a central venous catheter, particularly in candidates with risk factors and those similar to the present Borderline group.…”
Section: Discussionmentioning
confidence: 74%
“…However several studies have stated that CVP did not correlate with bleeding during the hepatectomy [19][20][21], Besides, there are potential fatal risks of low CVP strategies during hepatectomy include air embolism and tissue hypoperfusion [22], it was also reported by Jones et al [15] that a small air embolism was noticed in two patients (5% of patients with low CVP), Another important issue should be taken into consideration; the complication of central venous catheterization is from 5% to 26% in all patients required treatment and monitoring [23].…”
Section: Introductionmentioning
confidence: 89%